The Role of Incentives on the Performance of Health Workers in a Public Sector Organization in Abuja, Nigeria - Akpan, Nkereuwem (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The aim of the research work is to ascertain the role of incentives on the performance of health workers in some selected public sector using Abuja as a case study. Data collection was by the used of self-administered questionnaires, which were distributed to Doctors and Nurses in some selected public health facilities in Abuja. The statistical Package for Social Sciences (SPSS) software was used for data leaning and analysis. The result obtained from the analysis shows that 64.1% agreed that incentives brings job satisfaction, 51.4% agreed that non-monetary incentives promotes organizational performance , 63.3% agreed that non-monetary incentives promotes good work relationship, 53.7% agreed that non-monetary incentives reduces stress, 65.3% agreed that incentives help in the achievement of organizational goal, 58.7% agreed that incentives serve as a motivation to employees, 57.5% agreed that incentives help workers to improve skills and qualifications in line with their job and 60.2% agreed that incentives increase the level of employeeâ€™s confidence on employer. It was concluded that incentives based on terms and conditions of employment play significant role on the performance of health workers in the public sector, performance based incentives play significant role on the performance of health workers in the public sector, there is significant government attention towards incentives and performance of health care workers in the public sector and non-financial incentives play significant role on the performance of health workers in the public sector.Â